Jean Prouvé : the poetics of the technical object - Prouvé, Jean, (Vitra-Design-Museum, 2006)
Technical thought : Stiff Radar Tower, Ouessant Island / Jean Prouvé -- Technical thought, techniques of thinking / Bruno Reichlin -- Hands that see: The CNAM Lectures (1958-71) / Jean Louis Cohen -- Alphabet of structures / Benedikt Huber -- Jean Prouvé in detail: systems of assembly / Franz Graf -- The neoprene joint / Roberto Grignolo -- Joints and seals -- Notes on the Aluminium Centenary Pavilion / Jurg Conzett -- The asymmetrical 'crutch' of the Evian Pump Room / Catherine Dumont d'Ayot -- Serge Ketoff / Bernard Marrey -- Prouvé versus Mies: Alpexpo / Pean-Pierre Cetre -- Louis Fruitet / Bernard Marrey -- Tools and production methods : From the workshop to the ateliers / Catherine Coley -- Ironwork / Catherine Coley -- Robert Mallet-Stevens / Olivier Cinqualbre -- Tony Garnier / Dominique Chatelet -- Sheet metal and welding / Jean Prouvé -- Aero-Club Roland-Garros Buc, 1935-36 -- Maison du peuple, Clichy, 1935-39 -- Marcel Lods / Cuillemette Morel-Journel -- Vladimir Bodiansky / Olivier Cinqualbre -- Stainless steel / Jean Prouvé -- Promoting innovation / Florence Hachez-Leroy -- After Maxeville: from Avenue Kleber to Square Louvois (1954-57) / Michel Bataille -- CIMT / Catherine Coley -- Jean Swetchine / Bernard Marrey -- Prouvé as an engineering consultant and the Blanc-Manteaux Workshop / Laurence Allegret -- 'Factoried' houses, metal, wood, concrete : We need factoried houses / Jean Prouvé -- Prouvé, reconstruction, and the Saarland / Remi Baudoui -- The use of wood and the BCC House / Christian Sumi -- Pierre Jeanneret / Helene Bauchet-Cauquil -- André Sive / Olivier Cinqualbre -- Henri Prouvé / Vincent Bradel -- Tropical houses / Christian Enjolras -- African experimentation / Joseph Abram -- Central portal frames -- Bernard Laffaille and the development of the 'Prouvé-Shreds' / Nicolas Nogue -- The Nancy House / Tatsuo Iwaoka -- Shells -- Crutches -- Prouvé's involvement in the Unité d'habitation / Ruggero Tropeano -- Le Corbusier / Guillemette Morel-Journal -- Between 'bottle rack' and metabolism: Prouvé's concrete structures / Markus Peter -- Core constructions -- For industry / Shuichi Matsumura -- Demountable and mobile construction / Adolph Stiller -- An air of mobility / Pierre Lebrun -- Houses like cars? / François Chery -- Musee des beaux-arts du Havre: Jean Prouvé and LWD / Joseph Abram -- Experimenting with plastics / Philippe Bancilhon -- Jean Prouvé and Berlin's Freie Universitat / Peter Cachola Schmal and Ingeborg Flagge -- Other construction systems -- Factoried houses are comfortable houses / Franz Graf -- Furniture and interiors : Jean Prouvé's 'anti-design' / Jan van Geest -- Furniture -- Furniture, design, manufacture, marketing / Catherine Coley -- Charlotte Perriand / Charlotte Benton -- Jean Prouvé, UAM, and the Salon des arts meagers / Jacques Rouaud -- Jean Prouvé: the interiors / Arthur Ruegg -- Reception, legacy and biography : Reception, legacy, biography: the critical reception of Jean Prouvé's work / Guillemette Morel-Journel -- Reception in Japan / Yoshiyuki Yamana -- Junzo Sakakura: exchanges with Jean Prouvé / Yasuto Ota -- A prototypical legacy / Axel Venacque -- The Nancy School / Henri Claude -- Trajectories / Catherine Prouvé.